2020
DOI: 10.1556/1848.2020.20048
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid method technique for design and optimization of Formula race car exhaust muffler

Abstract: In this work a multilevel Computational Fluid Dynamics (CFD) analysis has been applied for the design of a Formula race car exhaust muffler with improved characteristics of sound pressure level (SPL) and fluid dynamic response. The approaches developed and applied for the optimization process range from the 1D to fully 3D CFD simulation, exploring hybrid approaches based on the integration of a 1D model with 3D tools. Modern mufflers typically have a complex system of chambers and flow paths. There are a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The study's findings suggested that using sound-absorbing material could lower SPL by 15% to 20%. [13][14][15] For automotive engines, Vasiraja and Saravana Sathiya Prabhahar 16 designed a muffler with perforated inner pipes and nozzles to reduce the sound pressure level. The investigation looked at the effect of convergence angle and nozzle number.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study's findings suggested that using sound-absorbing material could lower SPL by 15% to 20%. [13][14][15] For automotive engines, Vasiraja and Saravana Sathiya Prabhahar 16 designed a muffler with perforated inner pipes and nozzles to reduce the sound pressure level. The investigation looked at the effect of convergence angle and nozzle number.…”
Section: Introductionmentioning
confidence: 99%
“…The study's findings suggested that using sound-absorbing material could lower SPL by 15% to 20%. 13–15…”
Section: Introductionmentioning
confidence: 99%
“…Power-train and chassis consist of electrical powertrain component, braking system, engine component, cooling system, lubrication system, fuel system, steering system, transmission system suspension system and exhaust system [9]- [13]. Exhaust system is designed to convey the emission from the engine away from the driver and passengers and to reduce the emissions the vehicle releases into the environment [14], [15]. It control the delivery of hot gasses and provide information to the vehicle's computer in order to significantly improve vehicle performance and reduce the amount of noise generated by the vehicle.…”
Section: Introductionmentioning
confidence: 99%
“…It control the delivery of hot gasses and provide information to the vehicle's computer in order to significantly improve vehicle performance and reduce the amount of noise generated by the vehicle. The major components of the exhaust system include exhaust manifold, catalytic converter, exhaust pipe, resonator, muffler, oxygen sensors and tailpipe [12], [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the use of computational technology is used in this research. The use of computational technology in this research is the use of computational fluid dynamics software or abbreviated as CFD [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%